Design of Presence System as a Form of Monitoring Lecturer Attendance Data at UPT Labor PPNP - Syukriadi, Syukriadi - (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Presence system is an important thing in a government institution. With this system, a lecturer or employee will be bound by the rules and responsibilities that must be carried out. Lecturer attendance activities that carry out laboratory practicum activities at UPT labor Payakumbuh State Agricultural Polytechnic or PPNP have been available, but it is done on paper or paper based. During the lecturer's attendance recap procedure, the manager or head of UPT Labor considers this circumstance to be challenging and problematic. Furthermore, non-computerized attendance lists slow down reporting to the academic division, causing reporting to become fragmented, less effective, and less efficient. This research used R&D or Research and Development to solve the problem. While the development stage used the waterfall model with stages including: communication, planning, modeling, construction and deployment. As a result of this research, the lecturer presence system at UPT Labor has been tested using three types of testing: valid, practical, and effective tests. The validity test obtains an average value of 0.88, which is classified as valid, the product practicality test receives an average value of 0.90, which is classified as very practical criteria, and the effectiveness test obtains an average value of 0.94, which is classified as high effectiveness criteria. The lecturer presence system used in this study provides synergy with accurate attendance data, automatic attendance recap for reporting reasons, and minimizes errors during the recap process. Furthermore, reporting may be completed quickly, effectively, and efficiently.